(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic caused the remote teaching modality to be adopted as an emergency in Brazilian universities during the years 2020 and 2021. Most of the students were not used to the non-presential teaching, and several factors may have interfered in the learning process. This work aimed to analyze the impacts of the COVID-19 pandemic on the learning of undergraduate students in relation to the use of digital platforms. 292 students from the federal universities UFPI and UFRA participated in the research. Data collection took place through a questionnaire filled out online through the Google Forms platform. The results showed that 44% of the students repeatedly had learning difficulties during remote classes, with 74% attributing these difficulties to lack of concentration and 52% to the physical absence of the teacher. In addition, 51% of undergraduates did not have a quiet environment at home to study, and about three quarters of all graduates surveyed (74%) said they felt anxious, stressed and depressed, negatively impacted learning. It is concluded that the Covid-19 pandemic brought new challenges to the university community, showing reflections on the role and relevance of adopting hybrid curricula in future pedagogical projects in Higher Education Institutions.